Escandalosas: Plebeian Women and Violence in Venezuela’s Middle Period (1790-1860) - Zahler, Reuben (Anuario de Historia de América Latina, 2025)
This article investigates the meaning of scandal during Venezuela’s “middle-period”, from the end of the colony through the early republican decades ( 1780 - 1860). The article first attempts to understand the meaning of the term “scandal” during these years and then explores the phenomenon through an examination of court cases of women charged with violent crime. The investigation finds that historically the term “scandal” had a far more sinister meaning than it holds today. When used with reference to religion, politics, and state administration the term was associated with rebellion against institutions as well as the social hierarchies and cultural norms that supported those institutions. To accuse somebody of creating scandal implied that they harbored rebellious impulses and that they threatened social order because others might imitate the transgressor’s bad example. For a woman to be accused of scandalous behavior suggested that she had rebelled against patriarchal hierarchies, the honor code, and norms of feminine decency. Though scandal itself was not a crime, the courts treated scandal like a crime in order to preserve social order. Even if the court acquitted the woman of the crime for which she had been charged (i.e., murder), the judge would punish her for having scandalized the community. The defendants in these trials tended to be poor and illiterate. Their low socio-economic status left them particularly vulnerable to charges of scandalous behavior because any violation of feminine norms could appear as a rebellion against patriarchal hierarchy. Their low status also left them vulnerable to false accusations from relatives or neighbors, as simply the implication that she had caused scandal would hurt her reputation.